Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Sekretariat Daerah Kabupaten Garut - Pasyila Aulyana Nabilah; Bayu Seno Pitoyo; Dewi Sri Woelandari Giningroem (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The aim of this research is to determine the influence of the work environment and work motivation on employee performance at the Garut Regency Regional Secretariat Office. The type of research used in this research is quantitative research. The sampling technique used was probability sampling, namely 50 respondents. The data processing tool used in this research is SPSS software version 26. Based on the research results, it shows that work environment variables have a significant effect on employee performance at the Garut district regional secretariat office, and work motivation has a significant influence on employee performance at the Garut district regional secretariat office. The research results also show that work environment variables and work motivation simultaneously have a positive and significant effect on the performance of employees at the Garut Regency Regional Secretariat Office